Genome-wide screening and identification of new Trypanosoma cruzi antigens with potential application for chronic Chagas disease diagnosis. - João Luís Reis-Cunha (Public Library of Science (PLoS), 2014)
The protozoan Trypanosoma cruzi is the etiologic agent of Chagas disease, an infection that afflicts approximately 8 million people in Latin America. Diagnosis of chronic Chagas disease is currently based on serological tests because this condition is usually characterized by high anti-T. cruzi IgG titers and low parasitemia. The antigens used in these assays may have low specificity due to cross reactivity with antigens from related parasite infections, such as leishmaniasis, and low sensitivity caused by the high polymorphism among T. cruzi strains. Therefore, the identification of new T. cruzi-specific antigens that are conserved among the various parasite discrete typing units (DTUs) is still required. In the present study, we have explored the hybrid nature of the T. cruzi CL Brener strain using a broad genome screening approach to select new T. cruzi antigens that are conserved among the different parasite DTUs and that are absent in other trypanosomatid species. Peptide arrays containing the conserved antigens with the highest epitope prediction scores were synthesized, and the reactivity of the peptides were tested by immunoblot using sera from C57BL/6 mice chronically infected with T. cruzi strains from the TcI, TcII or TcVI DTU. The two T. cruzi proteins that contained the most promising peptides were expressed as recombinant proteins and tested in ELISA experiments with sera from chagasic patients with distinct clinical manifestations: those infected with T. cruzi from different DTUs and those with cutaneous or visceral leishmaniasis. These proteins, named rTc_11623.20 and rTc_N_10421.310, exhibited 94.83 and 89.66% sensitivity, 98.2 and 94.6% specificity, respectively, and a pool of these 2 proteins exhibited 96.55% sensitivity and 98.18% specificity. This work led to the identification of two new antigens with great potential application in the diagnosis of chronic Chagas disease.